1999
DOI: 10.1097/00004728-199903000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Niacin Therapy That Simulate Neoplasia: Hepatic Steatosis with Concurrent Hepatic Dysfunction

Abstract: Niacin, a widely used antihyperlipidemic agent, can produce hepatic steatosis and clinical hepatic abnormalities that together simulate the presentation of hepatobiliary neoplasia. We describe a patient initially suspected of having hepatobiliary neoplasia for whom imaging studies played a pivotal role in reaching the correct diagnosis of niacin-induced hepatotoxicity. Radiologists should become knowledgeable of these niacin-related effects, add niacin effects to the differential diagnosis of hepatic steatosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…46,[49][50][51][52][53][54][55] Our recent studies have shown that there is a strong lag-correlation between the prevalence of obesity and diabetes in the US population and the increased per capita consumption of niacin, which was attributed primarily to the consumption of fortified grains. 34,35 The toxic effects of niacin may involve a variety of mechanisms, including methyl depletion, changes in NAD-dependent reactions and excessive ROS generation.…”
Section: Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…46,[49][50][51][52][53][54][55] Our recent studies have shown that there is a strong lag-correlation between the prevalence of obesity and diabetes in the US population and the increased per capita consumption of niacin, which was attributed primarily to the consumption of fortified grains. 34,35 The toxic effects of niacin may involve a variety of mechanisms, including methyl depletion, changes in NAD-dependent reactions and excessive ROS generation.…”
Section: Arsenicmentioning
confidence: 99%
“…56 Interestingly, niacin has been found to induce both lipid-lowering effect 52 and adverse hepatic outcomes. 46,52,54,55 Thus, it seems that the lipidlowering effect of niacin may be mediated by methyl depletion, which, although improving cardiovascular outcomes, may increase the risk of adverse hepatic outcomes.…”
Section: Arsenicmentioning
confidence: 99%
“…There are additional reports of both niacin-induced lactic acidosis, especially associated with coingestion of alcohol and abnormal computed tomography scan images simulating hepatobiliary neoplasia. 3 Niacin can influence vascular function directly by modulating the activity of immune cells and endothelial cells. The mechanisms underlying the proangiogenic response remain to be determined.…”
mentioning
confidence: 99%